2018
DOI: 10.2298/pif1801019l
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of cinnamon and clove essential oils against button mushroom pathogens Cladobotryum dendroides (Bull.) W. Gams & Hooz and Lecanicillium fungicola var. fungicola (Preuss) Hasebrauk

Abstract: Antifungal activity of two essential oils, cinnamon (Cinnamomum verum J. Presl) and clove (Syzygium aromaticum (L.) Merrill & Perry), was evaluated against Cladobotryum dendroides (Bull.) W. Gams & Hooz, and Lecanicillium fungicola var. fungicola (Preuss) Hasebrauk, the causal agents of cobweb and dry bubble disease of cultivated mushroom. Inhibitory and fungicidal activity of the selected essential oils was assayed using three methods: microdilution, macrodilution fumigant and macrodilution contact method. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…[42][43][44] Clove oil contains eugenol up to 70-85% which is a phenolic compound with high antimicrobial activity. 40 The antifungal activity of the botanicals in the present study might be due to the presence of one or more bioactive compounds, such as alkaloids, glycosides, avonoids, steroids, and saponins. 45 The maximum intensive peak observed at 3375 cm À1 represented the OH groups; a peak at 1730 cm À1 and 1070 cm À1 represented the group C-O that is the characteristic band for alcohols and phenols; and a peak at 1643 cm À1 represented the aromatic carbonyl group belonging to quinine.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[42][43][44] Clove oil contains eugenol up to 70-85% which is a phenolic compound with high antimicrobial activity. 40 The antifungal activity of the botanicals in the present study might be due to the presence of one or more bioactive compounds, such as alkaloids, glycosides, avonoids, steroids, and saponins. 45 The maximum intensive peak observed at 3375 cm À1 represented the OH groups; a peak at 1730 cm À1 and 1070 cm À1 represented the group C-O that is the characteristic band for alcohols and phenols; and a peak at 1643 cm À1 represented the aromatic carbonyl group belonging to quinine.…”
Section: Discussionmentioning
confidence: 74%
“…38,39 Our results corroborate those of previous studies where clove and cinnamon essential oils were able to suppress mycopathogens, with clove oil exhibiting greater toxicity than cinnamon to Lecanicillium fungicola and Cladobotryum dendroides. 40 The bio-efficacy of botanicals is attributed to the fact that they have active compounds, such as azadirachtin, allicin, and salicin, which exhibit antifungal, antibacterial, and antiinsecticidal properties in nature. 41 Some research has also reported that botanical extracts and oils used in different concentrations can effectively control the mycelial growth of mycopathogens.…”
Section: Discussionmentioning
confidence: 99%
“…(Tanović et al, 2006;Glamočlija et al, 2006, Džamić et al, 2008Soković et al, 2009;Luković et al, 2018). Testing 18 EOs, Tanović et al (2006) found that thyme, cinnamon, clove and tea tree oils had the highest antifungal activity against these mycopathogenic fungi, while Luković et al (2018) found that clove and cinnamon completely inhibithed the growth of L. fungicola and Cladobotryum dendroides in tests that used three distinctive methods. Various EOs have been tested against various Trichoderma species, pathogens of cultivated mushrooms, and they demonstrated inhibitory effects in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, the experiments presented by Luković et al (2018) showed also the high sensitivity of L. fungicola to some essential oils. Inhibitory and fungicidal activity of the selected essential oils was assayed using microdilution and macrodilution fumigant methods.…”
Section: M9mentioning
confidence: 96%